Identification of risk factors for upper gastrointestinal bleeding in intensive care unit patients (GIBICU study). (2nd December 2022) - Poszler, Alexander; Nguyen, Evelyn; Braunisch, Matthias Christoph; Rasch, Sebastian; Abdelhafez, Mohamed; Ulrich, Jörg; Wiessner, Johannes; Schmid, Roland M.; Lahmer, Tobias
Abstract: Background and goals: Risk stratification for the need for therapeutic endoscopy and prediction of mortality in patients with upper gastrointestinal bleeding (UGIB) can be assessed by several scores. However, current scores are not validated for variceal bleeding and Intensive Care Unit (ICU) patients. The aim of this study was to evaluate potential parameters for the prediction of UGIB and patient outcomes. Patients and study methods: In this monocenter retrospective observational study, data from all esophagogastroduodenoscopies (EGD) between November 2014 and February 2020 with suspected hemorrhage in our ICU were evaluated. Results: Out of 345 included EGD, 42.3% of UGIB was diagnosed. 51.9% needed endoscopic intervention. Overall, 52.3% of included patients with UGIB died. Logistic regression showed that preceding variceal or non-variceal UGIB ( p < .001), serum lactate ( p = .001), heart rate (HR) ( p = .005), and blood transfusions ( p = .001) were significant predictors of UGIB. Previous UGIB ( p < .001), male sex ( p = .015), known varices ( p < .001), serum albumin ( p = .19) and use of catecholamines ( p = .040) were significant predictors for the need of endoscopic intervention. Higher mortality was significantly associated with the usage of steroids ( p < .001), malignant preconditions ( p = .021), serum albumin ( p = .020) and prolonged PTT (partial thromboplastin time) ( p = .001). Conclusions: We were able to identify additional parameters that had previously not been included in existing scores to predict the risk of UGIB, the need for therapeutic endoscopy and mortality in ICU patients. Therefore, an extension of these scores is necessary. Further validation of identified parameters in multicenter trials is needed to improve risk scores for ICU patients.